2013
DOI: 10.1038/cddis.2013.369
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII inhibition rectifies arrhythmic phenotype in a patient-specific model of catecholaminergic polymorphic ventricular tachycardia

Abstract: Induced pluripotent stem cells (iPSC) offer a unique opportunity for developmental studies, disease modeling and regenerative medicine approaches in humans. The aim of our study was to create an in vitro ‘patient-specific cell-based system' that could facilitate the screening of new therapeutic molecules for the treatment of catecholaminergic polymorphic ventricular tachycardia (CPVT), an inherited form of fatal arrhythmia. Here, we report the development of a cardiac model of CPVT through the generation of iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 43 publications
(65 reference statements)
5
85
0
Order By: Relevance
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…Interestingly, at the ultrastructural level, these symptoms were associated with alterations to various components of the intracellular energetic unit, including intercalated disk and microtubules. In addition, hiPSC-derived cardiomyocytes carrying mutations to ryanodine receptors (RyR2) calcium/calmodulin-dependent protein kinase II (CaMKII) and calsequestrin (CLSQ) displayed calcium oversensitization, the hallmark of catecholaminergic polymorphic ventricular tachycardia (CPVT) [181183]. Specifically, abnormalities in whole-cell calcium transients were observed, including proarrhythmic early/after depolarization events [181].…”
Section: Human Diseases-on-chips and The Intracellular Energetic Umentioning
confidence: 99%
“…12% of the cells also developed DADs even when paced at low frequencies of 0.5Hz, and the DAD frequencies increased significantly after β-adrenergic stimulation. Interestingly, CaMKII inhibitor KN-93 stabilized the Ca 2+ activity and suppressed isoproterenol-induced DAD in this model [65]. The P2328S CPVT1 causing mutation cell-line [43] also displays aberrant Ca 2+ cycling, decreased Ca 2+ content, and a fractional Ca 2+ release that was significantly higher both in control and isoproterenol-treated myocytes.…”
Section: Ca2+ Signaling Profiles Of Catecholaminergic Polymorphic mentioning
confidence: 99%